Pengaruh Luas Lahan, Biaya Produksi Dan Harga Pasar Terhadap Peningkatan Pendapatan Petani Bawang Merah Pada Saat Pandemi Covid 19 Di Desa Banaranwetan Kecamatan Bagor Kabupaten Nganjuk - Agus Susilo; Junaedi; Muhammad Mudjib Musta’in (Journal of Public Power, 2020)
Shallots are one of the leading commodity crops. The people of Banaranwetan village are very enthusiastic in planting shallots, besides the soil structure is very suitable, the lifespan of shallots is very short, only two months. The purpose of this study was to determine simultaneously and partially the effect of land area, production costs and labor market prices on shallot production in Banaranwetan Village, Bagor District, Nganjuk Regency. The type of research used is descriptive quantitative research and the research location is in Banaranwetan Village, Bagor District, Nganjuk Regency. The types of data used in this research are primary data and secondary data obtained from interviews, observations. The population taken by the researcher is all community members who work as farmers based on Family Cards (KK) in Banaranwetan Village, Bagor District, Nganjuk Regency. With a sample of 68 people. In this analysis using descriptive technique method. From the results of the study, it was found that there was an effect of land area, production costs and market prices on increasing the income of shallot farmers in Banaranwetan Village, Bagor District, Nganjuk Regency. The most dominant variable in increasing the income of shallot farmers in Banaranwetan village, Nganjuk Regency. is the selling price variable. This is evidenced by the partial measurement results that of the four independent variables that most influence the increase in farmers' income is the selling price.